2022
DOI: 10.3389/fphar.2022.809157
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid, A Critical Metabolite, Aggravates Cellular Senescence Through Reactive Oxygen Species Generation in Kawasaki Disease

Abstract: Coronary artery lesions (CALs) are severe complications of Kawasaki disease (KD), resulting in stenosis and thrombogenesis. Metabolomic profiling of patients’ plasma could assist in elucidating the pathogenesis of CALs and identifying diagnostic biomarkers, which are imperative for clinical treatment. The metabolic profiles between KD patients with CALs and without CALs (non-coronary artery lesion, or NCAL, group) indicated the most significantly differentially expressed metabolite, palmitic acid (PA), showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Extensive evidence substantiates the significant involvement of excess ROS production in the development of cardiovascular lesions during KD in children [23,24] and murine models [11,25] of KD vasculitis. Despite the existing anti-inflammatory approaches employed in the treatment of coronary artery abnormalities in KD, their therapeutic efficacy is currently limited, leading to suboptimal treatment outcomes [26,27].…”
Section: Discussionmentioning
confidence: 67%
“…Extensive evidence substantiates the significant involvement of excess ROS production in the development of cardiovascular lesions during KD in children [23,24] and murine models [11,25] of KD vasculitis. Despite the existing anti-inflammatory approaches employed in the treatment of coronary artery abnormalities in KD, their therapeutic efficacy is currently limited, leading to suboptimal treatment outcomes [26,27].…”
Section: Discussionmentioning
confidence: 67%
“…Besides the primary febrile symptoms, KD can lead to serious arterial lesions, and the prompt diagnosis of KD remains challenging 47 . Moreover, a recent study has indicated that KD can accelerate immune cell senescence through the generation of reactive oxygen species 48 . Therefore, we examined whether scRNA-seq data from KD, mapped to Panage_data, could capture KD-induced cellular senescence.…”
Section: Functional Shifting Of Inflammatory Myeloid Cells Is Associa...mentioning
confidence: 99%
“… 673 Furthermore, a study proven palmitic acid is a key metabolite as promising therapeutic target, which accelerates cellular senescence by producing living oxygen in kawasaki disease. 674 …”
Section: Functional Targetmentioning
confidence: 99%